Tuning Ion Transport at the Anode‐Electrolyte Interface via a Sulfonate‐Rich Ion‐Exchange Layer for Durable Zinc‐Iodine Batteries. Issue 13 (5th February 2023) - Zhang, Leiqian; Huang, Jiajia; Guo, Hele; Ge, Lingfeng; Tian, Zhihong; Zhang, Mingjie; Wang, Jingtao; He, Guanjie; Liu, Tianxi; Hofkens, Johan; Brett, Dan J.L.; Lai, Feili
Abstract: Rechargeable aqueous zinc‐iodine batteries (ZIBs) are considered a promising newly‐developing energy‐storage system, but the corrosion and dendritic growth occurring on the anode seriously hinder their future application. Here, the corrosion mechanism of polyiodide is revealed in detail, showing that it can spontaneously react with zinc and cause rapid battery failure. To address this issue, a sulfonate‐rich ion‐exchange layer (SC‐PSS) is purposely constructed to modulate the transport and reaction chemistry of polyiodide and Zn 2+ at the zinc/electrolyte interface. The resulting ZIBs can work properly over 6000 cycles with high‐capacity retention (90.2%) and reversibility (99.89%). Theoretical calculations and experimental characterization reveal that the SC‐PPS layer blocks polyiodide permeation through electrostatic repulsion, while facilitating desolvation of Zn(H2 O)6 2+ and restricting undesirable 2D diffusion of Zn 2+ by chemisorption. Abstract : An in‐depth understanding of the corrosion mechanism of polyiodide on zinc, leads to the development of a sulfonate‐rich ion‐exchange layer, to prevent polyiodide permeation, while also facilitating desolvation of Zn(H2 O)6 2+ and restricting the undesirable 2D diffusion of Zn 2+ . The resulting zinc‐iodine battery can work over 6000 cycles with good capacity retention (90.2%) and reversibility (99.89%).